COGNITIVE BEHAVIORAL THERAPHY - Muhammad Rouf Mustofa; Nurjannah (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2022)
In its current development, the CBT approach Theory has its own distinctive characteristics dealing with clients issues especially in Indonesia with various studies already done. One theory after another also has its own signature. Not infrequently, a counseling theories is no exception to CBT. The criticism of CBT it self is expressed in the journel written by revelation t Nanda Eka Saputra and Santi Widiasari titled acceptance and commitment thrapy: the new wave of cognitive behavior therapy, Indonesia Journal of school counseling, research by longmore & worrel, wich concludes that cognitive interventions. This study attemps to come up with a new theory or concept of CBT Islam with the weaknesses found in previous research. The journal review method is used by researchers to review some of the sources that discus historical, criticism, and the concept of improvement based on Islamic values